2020
DOI: 10.1002/nop2.657
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of social determinants of healthy lifestyle among Iranian women

Abstract: The World Health Organization (WHO) defines social determinants of health as the environment where people are born, grow, work and age (Marmot et al., 2008). This environment is shaped by the distribution of money, power and resources at the national, regional and global levels that are by themselves influenced by political choices. Social determinants account for a bulk of the inequities (unjust and avoidable differences in health status seen within countries) (WHO, 2020). Key social determinants of health in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…A healthy postoperative lifestyle increases the QOL of patients with liver cancer. Several studies have revealed the significant effect of postoperative complications on the QOL of patients with liver cancer [ 7 , 8 , 9 , 10 , 13 ], a finding that is consistent with that of this study. However, further research is warranted to elucidate the mechanism behind this effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A healthy postoperative lifestyle increases the QOL of patients with liver cancer. Several studies have revealed the significant effect of postoperative complications on the QOL of patients with liver cancer [ 7 , 8 , 9 , 10 , 13 ], a finding that is consistent with that of this study. However, further research is warranted to elucidate the mechanism behind this effect.…”
Section: Discussionsupporting
confidence: 93%
“…Due to advancements in medical technology, various treatment options are available for patients with liver cancer. However, after treatment, patients often experience less serious symptoms, such as pain, weight loss, fatigue, or nausea [ 2 , 3 , 4 , 5 , 6 ], to more serious symptoms, such as stomach discomfort and fever, loss of appetite, anxiety, or liver cancer recurrence, thereby affecting their quality of life (QOL) [ 7 , 8 , 9 , 10 ]. Studies have reported that patients with liver disease often have unhealthy habits.…”
Section: Introductionmentioning
confidence: 99%
“…At a psychological level, it can lead to low self-esteem, depression, and decreased quality of life. Our study focused on understanding the link between obesity and cognitive decline during long-term HD in middle-aged female rats since there is a higher rate of obesity in women, and they have a greater propensity to present dementia during advanced age ( Albanese et al, 2015 ; Ghasemi Yngyknd et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 According to a meta-analysis by Ghasemi et al, providing social support is one way to promote a healthy lifestyle among women. 8 Social support has three main types, namely (1) Emotional social support: having someone available to rely on and to trust when needed (2), Instrumental social support: the material, objective and real assistance received by an individual from others, and (3) Information social support: obtaining essential information through social interactions with others. 9 Individuals receiving social support enjoy several psychological benefits: their self-confidence is promoted, they feel empowered and efficient, and their quality of life is improved.…”
Section: Introductionmentioning
confidence: 99%